Aggressive Breast Cancer Treatment and Recovery - Garza, Elisa (Ars Medica, 2024)
These 3 poems seek to understand the body’s complex response to cancer treatment, as well as highlight lingering doubts about treatment outcomes in the face of physical and emotional reminders that cancer can always return.